Synapse-Specific Inhibitory Control of Hippocampal Feedback Inhibitory Circuit - Chamberland, Simon; Salesse, Charleen; Topolnik, Dimitry; Topolnik, Lisa (Frontiers in Cellular Neuroscience, 2010)
Local circuit and long-range GABAergic projections provide powerful inhibitory control over the operation of hippocampal inhibitory circuits, yet little is known about the input- and target-specific organization of interacting inhibitory networks in relation to their specific functions. Using a combination of two-photon laser scanning photostimulation and whole-cell patch clamp recordings in mice hippocampal slices, we examined the properties of transmission at GABAergic synapses formed onto hippocampal CA1 stratum oriens – lacunosum moleculare (O–LM) interneurons by two major inhibitory inputs: local projection originating from stratum radiatum interneurons and septohippocampal GABAergic terminals. Optical mapping of local inhibitory inputs to O–LM interneurons revealed that vasoactive intestinal polypeptide- and calretinine-positive neurons, with anatomical properties typical of type III interneuron-specific interneurons, provided the major local source of inhibition to O–LM cells. Inhibitory postsynaptic currents evoked by minimal stimulation of this input exhibited small amplitude and significant paired-pulse and multiple-pulse depression during repetitive activity. Moreover, these synapses failed to show any form of long-term synaptic plasticity. In contrast, synapses formed by septohippocampal projection produced higher amplitude and persistent inhibition and exhibited long-term potentiation induced by theta-like activity. These results indicate the input and target-specific segregation in inhibitory control, exerted by two types of GABAergic projections and responsible for distinct dynamics of inhibition in O–LM interneurons. The two inputs are therefore likely to support the differential activity- and brain state-dependent recruitment of hippocampal feedback inhibitory circuits in vivo, crucial for dendritic disinhibition and computations in CA1 pyramidal cells.